Robust dynamic grid emulator control. (July 2020) - Said-Romdhane, Marwa Ben; Skander-Mustapha, Sondes; Slama-Belkhodja, Ilhem
Abstract: This paper proposes an enhanced dynamic control strategy for a grid emulator. The proposed control switches between resonant and predictive controls in order to benefit from the advantages of both controls and to cope with their drawbacks. It ensures good dynamic performance in transient state and very low error in case of parametric or load variation during steady state. The most used control for grid emulator based on power converters is the one based on resonant controllers. Although this control is characterized by its robustness against parameters and load variation, it suffers from low performance in transient operation. The predictive control, which is characterized by its fast dynamic performance in transient state, can be used to overcome the resonant controllers limit. An exhaustive theoretical study reinforced by simulation and experimental results validate the capability, robustness and high performances of the proposed dynamic control strategy.